PENGARUH UKURAN PERUSAHAAN, LAVERAGE, PROFITABILITAS, MARKET TO BOOK RATIO, KEPEMIIKAN MAYORITAS DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Puji Rahayu (Accounting Global Journal, 2017)
This  research meant to test the influence of the characteristic of the company and the corporate social responsibility to the aggressiveness tax of a company. Characteristic of the company uses firm size, laverage, and inventory intensity. The population of this research is the entire manufacturing companies which are listed in Indonesia Stock Exchange (IDX). The sample collection technique has been done by using purposive sampling and 32 companies have been obtained as sample criteria during 2010-2014. The hypothesis test has been done by using multiple linear regressions analysis technique. The result of this research shows that firm size, laverage, and corporate social responsibility have significant influence to the tax aggressiveness; it mean that the size of a company, liability and level of corporate social responsibility will influence the tax aggressiveness level in each company. Laverage uses debt to minimize tax burden of companies even more likely to lead aggressively against the corporation tax. Meanwhile profitability, market to book ratio and majority firm does not have any influence to the tax agggressiveness, it means company prefer to increase the profit instead of meet the tax burden and when the the company stock is decreased, investors will not invest in that company.